Functionalized Graphdiyne Nanowires: On‐Surface Synthesis and Assessment of Band Structure, Flexibility, and Information Storage Potential. Issue 14 (6th February 2018) - Klappenberger, Florian; Hellwig, Raphael; Du, Ping; Paintner, Tobias; Uphoff, Martin; Zhang, Liding; Lin, Tao; Moghanaki, Bahare Abedin; Paszkiewicz, Mateusz; Vobornik, Ivana; Fujii, Jun; Fuhr, Olaf; et al.
Abstract: Carbon nanomaterials exhibit extraordinary mechanical and electronic properties desirable for future technologies. Beyond the popular sp 2 ‐scaffolds, there is growing interest in their graphdiyne‐related counterparts incorporating both sp 2 and sp bonding in a regular scheme. Herein, we introduce carbonitrile‐functionalized graphdiyne nanowires, as a novel conjugated, one‐dimensional (1D) carbon nanomaterial systematically combining the virtues of covalent coupling and supramolecular concepts that are fabricated by on‐surface synthesis. Specifically, a terphenylene backbone is extended with reactive terminal alkyne and polar carbonitrile (CN) moieties providing the required functionalities. It is demonstrated that the CN functionalization enables highly selective alkyne homocoupling forming polymer strands and gives rise to mutual lateral attraction entailing room‐temperature stable double‐stranded assemblies. By exploiting the templating effect of the vicinal Ag(455) surface, 40 nm long semiconducting nanowires are obtained and the first experimental assessment of their electronic band structure is achieved by angle‐resolved photoemission spectroscopy indicating an effective mass below 0.1 m 0 for the top of the highest occupied band. Via molecular manipulation it is showcased that the novel oligomer exhibits extreme mechanical flexibility and opens unexplored ways of information encoding in clearly distinguishable CN‐phenyl trans–cis species. Thus, conformational data storage with density of 0.36 bit nm −2 and temperature stability beyond 150 K comes in reach. Abstract : Carbonitrile‐functionalized graphdiyne nanowires are fabricated by on‐surface synthesis . The scanning probe and photoelectron characterization demonstrates that the nanowires represent a novel conjugated, 1D carbon nanomaterial featuring an effective mass below 0.1 m 0 for the top of the highest occupied band. Tip manipulation showcases the extreme flexibility and novel ways of information encoding in trans – cis conformers.